2010
DOI: 10.1037/a0019844
|View full text |Cite
|
Sign up to set email alerts
|

Associations of marijuana use and sex-related marijuana expectancies with HIV/STD risk behavior in high-risk adolescents.

Abstract: Multiple studies suggest an association of marijuana use with increased rates of sexual risk behavior and sexually transmitted diseases (STDs). Most studies have focused on global associations of marijuana use with sexual risk outcomes and few have examined relevant cognitive variables. Adolescents in the juvenile justice system are at elevated risk for HIV/STDs and preliminary evidence suggests that marijuana is a potentially important cofactor for sexual risk behavior in this population. This study evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 62 publications
6
94
0
Order By: Relevance
“…In another study, high-risk African American adolescents expected more sexual enhancement from marijuana relative to alcohol use and stronger marijuana enhancement expectancies were associated with more frequent use in sexual situations (Kingree & Thompson, 2007). These findings were supported and extended in yet another study among high-risk adolescents, whereby stronger sex-related marijuana enhancement expectancies predicted greater frequency marijuana use in sexual situations, and event-level analyses revealed that marijuana use predicted lack of condom use (Hendershot, Magnan, & Bryan, 2010). Thus, marijuana and alcohol use typologies may be associated with unique sexual risk outcomes according to sex-related expectancies.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…In another study, high-risk African American adolescents expected more sexual enhancement from marijuana relative to alcohol use and stronger marijuana enhancement expectancies were associated with more frequent use in sexual situations (Kingree & Thompson, 2007). These findings were supported and extended in yet another study among high-risk adolescents, whereby stronger sex-related marijuana enhancement expectancies predicted greater frequency marijuana use in sexual situations, and event-level analyses revealed that marijuana use predicted lack of condom use (Hendershot, Magnan, & Bryan, 2010). Thus, marijuana and alcohol use typologies may be associated with unique sexual risk outcomes according to sex-related expectancies.…”
Section: Introductionmentioning
confidence: 72%
“…Thus, marijuana and alcohol use typologies may be associated with unique sexual risk outcomes according to sex-related expectancies. In particular, use of alcohol for social enhancement may be associated with a greater number of partners (Cooper, 2002;Khan et al, 2012;Seth et al, 2011) and use of marijuana for sexual enhancement may be associated with lack of condom use (Hendershot et al, 2010;Kingree, Braithwaite, & Woodring, 2000).…”
Section: Introductionmentioning
confidence: 97%
“…50,51 Moreover, a critical intervention point may be attitudes, self-efficacy, and expectancies about future behavior, as recent studies have suggested that cognitive processes mediate marijuana use and risky sexual behavior among adolescent offenders. 52 The study findings suggest that it would be advisable to extend these interventions to address methamphetamine use, given its association with high-risk sexual behaviors in this sample. Additionally, the disproportionate number of juvenile offenders who are ethnic minorities requires a sensitivity to and awareness of the need for programs that take into account the role of culture and ethnicity on assessment, intervention, and treatment in juvenile justice settings.…”
Section: Implications For Public Health Programmingmentioning
confidence: 99%
“…Similarly, substance use is often initiated during adolescence and peaks during emerging adulthood (Arnett, 2000(Arnett, , 2005Stone et al, 2012; Substance Abuse and Mental Health Services Administration [SAMHSA], 2011). Alcohol and other drug use have been associated with SRBs in samples of young people at both the global level, perhaps refl ecting problem behavior theory (Donovan, 1996;Jessor, 1982) in which risk behaviors tend to cluster, and the event level (Bonar et al, in press;Brown and Vanable, 2007;Bryan et al, 2007Bryan et al, , 2012Ellickson et al, 2005;Hendershot et al, 2010;Kiene et al, 2009;Nkansah-Amankra et al, 2011), likely refl ecting contextual infl uences and acute intoxication that may affect decision making related to SRBs.…”
mentioning
confidence: 99%